2-Keto-L-Gulonic Acid Improved the Salt Stress Resistance of Non-heading Chinese Cabbage by Increasing L-Ascorbic Acid Accumulation - Gao, Mingfu; Sun, Hao; Shi, Meijun; Wu, Qiqi; Ji, Dongxu; Wang, Bing; Zhang, Lixin; Liu, Yang; Han, Litao; Ruan, Xicheng; Xu, Hui; Yang, Weichao (Frontiers in Plant Science, 2021)
Salt stress has long been a prominent obstacle that restricts crop growth, and increasing the L-ascorbic acid (ASA) content of crops is an effective means of alleviating this stress. 2-Keto-L-gulonic acid (2KGA) is a precursor used in industrial ASA production as well as an ASA degradation product in plants. However, to date, no study has investigated the effects of 2KGA on ASA metabolism and salt stress. Here, we evaluated the potential of using 2KGA to improve crop resistance to salt stress (100mM NaCl) through a cultivation experiment of non-heading Chinese cabbage (Brassica campestris ssp. chinensis). The results showed that the leaf and root biomass were significantly improved by 2KGA application. The levels of metabolites and enzymes related to stress resistance were increased, whereas the hydrogen peroxide (H2O2) and malondialdehyde (MDA) contents were decreased. Lipid peroxidation and cell membrane damage were alleviated following 2KGA treatment. Positive correlations were found between photosynthetic pigments and organic solutes, ASA and photosynthetic pigments, and ASA and antioxidant enzymes. In contrast, negative correlations were observed between antioxidant enzymes and H2O2/MDA. Moreover, the expression levels of L-gulono-1,4-lactone oxidase, GDP-mannose pyrophosphorylase, dehydroascorbate reductase-3, and ascorbate peroxidase were increased by 2KGA treatment. These results suggested that exogenous 2KGA application can relieve the inhibitory effect of salt stress on plant growth, and the promotion of ASA synthesis may represent a critical underlying mechanism. Our findings have significant implications for the future application of 2KGA or its fermentation residue in agriculture.